Glycyrrhetinic Acid Maintains Intestinal Homeostasis via HuR - Chen, Gang; Bei, Bei; Feng, Yuan; Li, Xuezheng; Jiang, Zhe; Si, Jian-Yong; Qing, De-Gang; Zhang, Juan; Li, Ning (Frontiers in Pharmacology, 2019)
Glycyrrhetinic acid (GA) is one of the main components for the traditional medicine of licorice, which can synchronize and promote effects of other medicines in the traditional prescription. In this paper we found GA could promote IEC-6 cell proliferation, rescue the proliferative inhibition caused by DFMO, decrease the apoptotic rate, and reverse the delay in restitution after wounding caused by DMFO in IEC-6 cells via HuR. To be noted, GA failed to promote proliferation and to suppress apoptosis after silencing HuR by siRNA in IEC-6 cells. Furthermore, with the model of small intestinal organoids developed from intestinal crypt stem cells, we found GA could increase HuR and its downstream ki67 levels to promote intestinal organoid development. Last, GA was substantiated to be able to maintain the integrity of the intestinal epithelium under the circumstance of 48 h-fasting in rat via raising HuR and its downstream genes such as EGF, EGFR, and MEK. These results suggested that via Hur modulation, GA could promote intestinal epithelium homeostasis, and therefore contributing to the absorption in small intestine of constituents from other medicines co-existing in the traditional prescription with licorice. Our results provided a new perspective for understanding the synchronization effect of licorice.